Antioxidant Potency of Herbal Plants Against Degenerative Disease Progression - Khayru, Rafadi Khan (Journal of Social Science Studies, 2022)
Herbal plants have long been recognized for their therapeutic properties, particularly in mitigating oxidative stress associated with degenerative diseases. This literature-based investigation explores five major antioxidant-rich herbs—Camellia sinensis, Curcuma longa, Rosmarinus officinalis, Ginkgo biloba, and Allium sativum—and the scientific mechanisms underlying their protective effects. Findings reveal that these herbs exert their actions through modulation of redox-sensitive pathways such as Nrf2-ARE, inhibition of pro-inflammatory enzymes, and enhancement of mitochondrial integrity. Synergistic combinations of phytochemicals further augment their antioxidative capacity. While these plants offer promising interventions, their clinical utility is contingent upon factors such as bioavailability and pharmacokinetics. The review calls for expanded clinical trials and interdisciplinary research to validate efficacy and optimize therapeutic use. Understanding the phytopharmacological interactions and biochemical pathways of herbal antioxidants is essential for incorporating them into integrative preventive healthcare. These insights underscore the significance of bridging traditional knowledge and scientific rigor to develop sustainable health strategies.